Review of flood disaster studies in Nepal: A remote sensing perspective. (March 2019) - Pangali Sharma, Til Prasad; Zhang, Jiahua; Koju, Upama Ashish; Zhang, Sha; Bai, Yun; Suwal, Madan Krishna
Abstract: Research on flood disaster generate ideas and provoke the best solution for disaster management. This work primarily focuses research on monsoon flood due to its frequency and severity in the southern flood plain of Nepal. Here we review the previous studies on flood disaster at the regional and national level and compare with the global context. This facilitates exploring the data and methods that are mostly unexplored, and areas that have not lightened in the field of flood studies in Nepal. Our scope of literature review limited the literature that are accessed through internet. The findings are revised and compared with different contexts. Multi-criteria weighted arithmetic mean have been used to find the spatial severity of flood disaster in 2017. We found several studies carried out on flood in Nepal. They are mostly based on field-based data, except few that have used current state-of-art, remote sensing method, using satellite images. Since the multi-spectral optical satellite imageries have a high cloud effect, it is not very useful in real time flood mapping; and very limited Synthetic-Aperture Radar (SAR) image, has been used in Nepal. In Global context, Support Vector Machine and Random Forest method are used in flood risk assessment; VNG flood V1.0 software has been used in flood forecasting, and Probabilistic Change Detection and Thresholding have widely been used in flood research, which can also be adopted in Nepalese context. Highlights: Multi-Criteria evaluation method is being used for spatial severity disaster mapping in Nepal. Monsoon flood related studies in Nepal, their data and methods are critically analysed. Recent remote sensing data and methods, which is very essential for effective and timely disaster management, are hardly used in flood disaster management in Nepal.